2014
DOI: 10.1152/japplphysiol.01291.2013
|View full text |Cite
|
Sign up to set email alerts
|

Defining a stimuli-response relationship in compensatory lung growth following major resection

Abstract: Major lung resection is a robust model that mimics the consequences of loss-of-functioning lung units. We previously observed in adult canines, following 42% and 58% lung resection, a critical threshold of stimuli intensity for the initiation of compensatory lung growth. To define the range and limits of this stimuli-response relationship, we performed morphometric analysis on the remaining lobes of adult dogs, 2-3 years after surgical removal of ∼ 70% of lung units in the presence or absence of mediastinal sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 56 publications
2
29
0
Order By: Relevance
“…The occurrence of compensatory lung growth (CLG) after pneumonectomy has been known for many years and can be induced in various species (29, 50, 154). Ravikumar et al (123,124) addressed various interesting mechanistic questions of CLG by assessing the structures of the remaining lung tissue by design-based stereology. In the first paper (123), the authors investigated the effects of two mechanical stimuli on the extent of CLG, namely the increased perfusion of the remaining lung and the lateral expansion due to mediastinal shift.…”
Section: Biological Observations Obtained By Stereological Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of compensatory lung growth (CLG) after pneumonectomy has been known for many years and can be induced in various species (29, 50, 154). Ravikumar et al (123,124) addressed various interesting mechanistic questions of CLG by assessing the structures of the remaining lung tissue by design-based stereology. In the first paper (123), the authors investigated the effects of two mechanical stimuli on the extent of CLG, namely the increased perfusion of the remaining lung and the lateral expansion due to mediastinal shift.…”
Section: Biological Observations Obtained By Stereological Methodsmentioning
confidence: 99%
“…The data on volume expansion by high resolution CT and on various alveolar components by stereology enabled the authors to attribute certain portions of CLG to either the increased lung perfusion or the lateral expansion. The second paper (124) analyzed the degree of CLG after different amounts of lung resection (42,58, and 65-70%) to see if a stimulus-response relationship exists. The stereological data showed that CLG peaks with 58% and is less extensive after 70% lung resection, which the authors hypothesized to be related to mechanical stress that threatens the integrity of alveolar septa.…”
Section: Biological Observations Obtained By Stereological Methodsmentioning
confidence: 99%
“…Thereafter, re-initiation of lung growth/regeneration requires changes in mechanical signals and the availability of space for the lung to grow. This can be provided experimentally by the process of unilateral pneumonectomy (PNX)(Dane et al, 2013; Ravikumar et al, 2013; Ravikumar et al, 2014). In this procedure in mice the single left lobe is removed, leaving the four right lobes intact.…”
Section: Remodeling and Regrowth Of The Alveolar Region After Pneumonmentioning
confidence: 99%
“…In contrast, large mammals such as dogs rely heavily on the recruitment of their extensive physiological reserves; regeneration of new alveolar-capillary tissue, a metabolically costly option, is invoked only when existing reserves are exhausted. In both small and large species, compensatory lung growth is more easily invoked and more vigorous in young actively growing animals than in mature adults (274, 297, 338); the difference reflects the small microvascular reserves in immature lungs as well as the greater plasticity of the immature thorax as the enlarging ribcage creates space to permit lung growth without causing distortion. Another factor that influences the ease of growth reinitiation is the age at which epiphyseal union of the ribs occurs.…”
Section: Induced Structural Adaptation and Its Functional Consequencesmentioning
confidence: 99%